1905 N.Y. Laws 129-30 - (:unkn) unknown (My University, 1905)
Ch. 92, § 2: Prohibited anyone over the age of sixteen to carry or carry concealed any pistol, revolver, or other firearm without a licensed issued by a police magistrate. Also prohibited the use against another, carry, or possession of slung-shot, billy, sandclub, metal knuckles, dagger, or dangerous knife is guilty of a felony.
Keywords: CARRY - CONCEALED; POSSESSION - NON-GUN ARMS